2011
DOI: 10.1186/1471-230x-11-97
|View full text |Cite
|
Sign up to set email alerts
|

The value of age and medical history for predicting colorectal cancer and adenomas in people referred for colonoscopy

Abstract: BackgroundColonoscopy is an invasive and costly procedure with a risk of serious complications. It would therefore be useful to prioritise colonoscopies by identifying people at higher risk of either cancer or premalignant adenomas. The aim of this study is to assess a model that identifies people with colorectal cancer, advanced, large and small adenomas.MethodsPatients seen by gastroenterologists and colorectal surgeons between April 2004 and December 2006 completed a validated, structured self-administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 27 publications
2
30
1
1
Order By: Relevance
“…Family history was self-reported and not systematically verified, and indications for colonoscopy were extracted from admission notes. Allowing for these limitations, results showed that adenoma prevalence rises with age, and this is in keeping with what would be expected in the general population [53]. This report also confirms a recent publication demonstrating that advanced polyps in patients under 45 are more likely to be sporadic than associated with family history, as family history of CRC was reported in 7.1% of those with any advanced neoplasia [54].…”
Section: Discussionsupporting
confidence: 88%
“…Family history was self-reported and not systematically verified, and indications for colonoscopy were extracted from admission notes. Allowing for these limitations, results showed that adenoma prevalence rises with age, and this is in keeping with what would be expected in the general population [53]. This report also confirms a recent publication demonstrating that advanced polyps in patients under 45 are more likely to be sporadic than associated with family history, as family history of CRC was reported in 7.1% of those with any advanced neoplasia [54].…”
Section: Discussionsupporting
confidence: 88%
“…12 The correlation between colonic neoplasia with lower gastrointestinal (GI) symptoms is poor, and population investigation based on symptoms alone is not recommended. [15][16][17] Current CRC screening programs do not all stratify for established CRC risk factors beyond age, such as family history, sex, smoking status, and body mass index (BMI). [7][8][9][10][11] Incorporating simple demographic factors to screen appropriately at-risk populations or triaging those with risk factors may improve health care utilization by reducing futile colonoscopies.…”
Section: Introductionmentioning
confidence: 99%
“…The cost of unnecessary normal colonoscopy is substantial, and the potential cost saving of more efficient triage of colonoscopy is large. There is poor correlation between colonic polyps and lower gastrointestinal (GI) symptoms, and symptom‐based screening is not recommended . Current screening programs do not stratify for established risk factors other than age; such as family history, sex, smoking status, and body mass index (BMI).…”
Section: Patient Selectionmentioning
confidence: 99%
“…There is poor correlation between colonic polyps and lower gastrointestinal (GI) symptoms, and symptom-based screening is not recommended. [33][34][35] Current screening programs do not stratify for established risk factors other than age; such as family history, sex, smoking status, and body mass index (BMI). Some countries have adopted fecal occult blood test (FOBT) screening to decrease the burden of colonoscopy.…”
Section: Patient Selectionmentioning
confidence: 99%